2015
DOI: 10.1038/srep17303
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility between mitochondrial and nuclear genomes correlates with the quantitative trait of lifespan in Caenorhabditis elegans

Abstract: Mutations in mitochondrial genome have epistatic effects on organisms depending on the nuclear background, but a role for the compatibility of mitochondrial-nuclear genomes (mit-n) in the quantitative nature of a complex trait remains unexplored. We studied a panel of recombinant inbred advanced intercrossed lines (RIAILs) of C. elegans that were established from a cross between the N2 and HW strains. We determined the HW nuclear genome content and the mitochondrial type (HW or N2) of each RIAIL strain. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…Sharing of physiology should be informative for a phonetic approach of phylogeny. Coevolution of mtDNA, Y, and autosomes has been found by many previous studies (25,(65)(66)(67)(68), which may play a key role in the diversification into multiple haplotypes during AMH radiation from its place of origin to other regions by hybridization with archaic humans. People who have stayed relatively unchanged in physiology and living environments from the ancestor would be expected to have few deviations from the ancestor haplotype and their present day living place would indicate place of origin for the ancestor.…”
Section: Molecular and Other Types Of Evidence For The New Modelmentioning
confidence: 71%
See 3 more Smart Citations
“…Sharing of physiology should be informative for a phonetic approach of phylogeny. Coevolution of mtDNA, Y, and autosomes has been found by many previous studies (25,(65)(66)(67)(68), which may play a key role in the diversification into multiple haplotypes during AMH radiation from its place of origin to other regions by hybridization with archaic humans. People who have stayed relatively unchanged in physiology and living environments from the ancestor would be expected to have few deviations from the ancestor haplotype and their present day living place would indicate place of origin for the ancestor.…”
Section: Molecular and Other Types Of Evidence For The New Modelmentioning
confidence: 71%
“…Seemingly unexpectedly, certain Neanderthals found in Europe is most closely related to Asians (Vi33. 25) or Americans (Vi33.26), and one of the three Neanderthals closest to Africans was closer to East Asians than to Europeans. However, this would be expected if Africans associated with the Neanderthal exit had entered Asia or South Asia via the Northern route from Siberia or possibly a Southern route.…”
Section: Cc-by-ncmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, polymorphisms in a mitochondrial‐encoded tRNA and a nuclear‐encoded tRNA synthetase, which are independently silent, cause significant developmental and reproductive defects in flies when combined . In worms, association mapping in a panel of hybrids, generated by a cross between C. elegans strains (N2 and HW), indicated that the quantitative trait of aging may depend on genome‐wide quantitative variations in mitonuclear genomic compatibility . Interspecies cytoplasmic–nuclear hybrids (cybrids) within Caenorhabditis briggsae showed that mitonuclear discord can reduce fecundity, increase adiposity, and elevate ROS levels .…”
Section: The Instructions For Life Are Split and Encoded In Two Separmentioning
confidence: 99%